2012
DOI: 10.1007/s13566-012-0054-7
|View full text |Cite
|
Sign up to set email alerts
|

Delayed radiation therapy timing and use of intensity-modulated radiation therapy in non-head and neck pediatric rhabdomyosarcoma

Abstract: Objective The impact of radiation therapy (RT) timing and use of intensity-modulated radiation therapy (IMRT) in nonhead and neck pediatric rhabdomyosarcoma (RMS) is underreported. Methods Children with non-head and neck RMS treated definitively with chemotherapy and RT from December 2000 through May 2010 at our institution were identified for analysis. Kaplan-Meier estimates of time to local progression-free survival (PFS), disease-free survival, and overall survival were performed, and Cox proportional hazar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Retrospective analyses of data from IRSG studies as well as multiple single‐institution series have assessed the impact of RT timing on local control (LC). Some studies suggest that early initiation of RT is important for LC in patients with meningeal impingement,3 whereas other investigations have demonstrated that delay of RT by 16 weeks or even longer may not compromise outcomes in patients with parameningeal (PM) RMS 4‐6…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective analyses of data from IRSG studies as well as multiple single‐institution series have assessed the impact of RT timing on local control (LC). Some studies suggest that early initiation of RT is important for LC in patients with meningeal impingement,3 whereas other investigations have demonstrated that delay of RT by 16 weeks or even longer may not compromise outcomes in patients with parameningeal (PM) RMS 4‐6…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that early initiation of RT is important for LC in patients with meningeal impingement, 3 whereas other investigations have demonstrated that delay of RT by 16 weeks or even longer may not compromise outcomes in patients with parameningeal (PM) RMS. [4][5][6] More recently, the development of advanced RT techniques, such as diagnostic image fusion for target delineation and intensity-modulated radiation therapy (IMRT) with daily image guidance, have enabled the confident delivery of more conformal treatments with the possibility of reduced margins for treatment uncertainties. Several institutions have now reported promising clinical experience with IMRT for pediatric RMS.…”
Section: Introductionmentioning
confidence: 99%
“…1,7 For EpSSG standard RT for RMS is delivered in once daily fractions to doses between 36 and 50.4Gy, varying according to the tumor histology, tumor response and IRS group. 7,8 Although the benefit of RT is widely accepted, no consensus guidelines exist regarding specific radiation therapy parameters such as the use of IMRT in non-head and neck RMS. In a recent but limited retrospective review analyzing, inter alia, the impact of the use of IMRT on local control in pediatric patients with non-head and neck RMS, authors found no negative effect of the use of IMRT on local control.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, further analysis is required to evaluate the direct effects of this RT variable on treatment effectiveness as well as on treatment toxicity in non-head and neck RMS including biliary RMS. 8 Regarding medical treatment, all patients with biliary RMS receive chemotherapy based on the risk grouping. In the children's oncology group COG, the risk stratification system incorporates pretreatment staging, the extent of disease after surgical resection (clinical group).…”
Section: Discussionmentioning
confidence: 99%